2013
DOI: 10.4314/ahs.v13i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Underlying congenital heart disease in Nigerian children with pneumonia

Abstract: Background: Pneumonia is a common cause of childhood morbidity and mortality globally. Some congenital heart disease (CHD) may predispose their sufferer to bronchopneumonia. Objective: To evaluate the contribution of CHD to pneumonia in children seen in a tertiary hospital. Methods: Over a year, consecutive children diagnosed radiologically with pneumonia were evaluated echocardiographically for CHD. Certain characteristics in children with pneumonia and CHD were compared to those without CHD. Results: There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 12 publications
0
30
1
1
Order By: Relevance
“…Similarly, a Nigerian case–control study reported a prevalence of HF of 82.2% among 73 children with congenital heart disease (90.4% of these 73 children were malnourished) compared with none among 76 children without congenital heart disease (21.1% of these 76 children were malnourished) (Table 3 ) [ 35 ]. Another prospective study, from Nigeria, reported a 64.3% prevalence of HF among 14 children with congenital heart disease and pneumonia compared with 37.4% among 107 children without congenital heart disease, but with pneumonia (Table 3 ) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a Nigerian case–control study reported a prevalence of HF of 82.2% among 73 children with congenital heart disease (90.4% of these 73 children were malnourished) compared with none among 76 children without congenital heart disease (21.1% of these 76 children were malnourished) (Table 3 ) [ 35 ]. Another prospective study, from Nigeria, reported a 64.3% prevalence of HF among 14 children with congenital heart disease and pneumonia compared with 37.4% among 107 children without congenital heart disease, but with pneumonia (Table 3 ) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…A high HF prevalence was observed when congenital heart disease co-existed with conditions such as malnutrition, pneumonia, and trisomy 21 [ 26 , 35 , 37 , 39 , 91 ]. Findings from these studies also suggest that spontaneous closure of ASDs/VSDs was less common in young children with co-existing HF than in those without HF [ 33 , 36 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which recurrent chest infections cause heart failure has been postulated by Sadoh. It was suggested that, with pulmonary overcirculation and pulmonary edema associated with large left to right shunting of blood, pulmonary congestion ultimately becomes a focus of infection in the lower respiratory tract [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Co-existence between cardiac failure and pneumonia was described by Sado indicating that excess pulmonary congestion in heart failure, acting as a nidus of infection leading to lower respiratory tract infection ( 7 ). The association between vitamin D deficiency and increased risk of lower respiratory tract infection has also been described in children ( 8 ).…”
Section: Discussionmentioning
confidence: 96%